Analysis Of The Impact Of Esg (Environmental, Social, Governance) On Company Financial Performance In Indonesia Post-Green Taxonomy Implementation - Antoni, Antoni (Amkop Management Accounting Review (AMAR), 2024)
This study aims to analyze the impact of ESG (Environmental, Social, and Governance) dimensions on the financial performance of companies in Indonesia following the implementation of the Green Taxonomy by the Financial Services Authority (OJK). ESG is an important indicator in assessing the sustainability and responsibility of a company, while financial performance is measured using indicators such as Return on Assets (ROA), Return on Equity (ROE), and Tobin’s Q. The approach used is explanatory quantitative with secondary data obtained from sustainability reports and annual financial statements of non-financial public companies listed on the Indonesia Stock Exchange (IDX) during the post-implementation period of the Green Taxonomy. The analysis technique used is panel data regression with Fixed Effect or Random Effect models, accompanied by classical assumption tests and significance tests. The research results show that the three aspects of ESG simultaneously and partially have a significant impact on the company's financial performance. These findings reinforce the importance of adopting ESG as part of long-term business strategies and demonstrate the strategic role of the Green Taxonomy in promoting sustainability integration in Indonesia's corporate sector.